Complement system-related genes in stomach adenocarcinoma: Prognostic signature, immune landscape, and drug resistance - Tong, Xiaoxia; Yang, Xiaohu; Tong, Xiaojuan; Zhai, Dong; Liu, Yonglei (Frontiers in Genetics, 2022)
Stomach adenocarcinoma (STAD) is one of the most common malignant tumors of the digestive tract, and its survival predictors are critical for precision medicine but have not been fully investigated. The complement system is a complex multistep cascade at the interface of innate and adaptive immunity, which augments the function of antibodies and phagocytes. This study aimed to construct and validate a CSRGs signature based on TCGA (The Cancer Genome Atlas) STAD dataset, and revalidated it in an external GEO (Gene Expression Omnibus) STAD cohort. Subsequently, we assessed the association of risk levels with the stromal and immune cells infiltration level in STAD using the ESTIMATE, Single Sample Gene Set Enrichment Analysis (SSGSEA) and (Microenvironment Cell Populations-counter) MCPcounter algorithm. It was found that the CSRGs signature, based on three genes (SERPINE1, PROC and CFHR3), was significantly and independently associated with the OS in TCGA STAD patients (P<0.001). Subsequently, we found that the high-risk STAD harbors more immune cell infiltration than the low-risk group, and the ESTIMATE results indicated that there exists a more stromal component in the tumor microenvironment of the high-risk groups. Compared to the low-risk group, high-risk STAD patients had higher expressions of marker genes for immune checkpoint inhibitors (ICIs) and showed higher sensitivity to the chemotherapy agents (Rapamycin, Nilotinib, 5-Fluorouracil, Axitinib, DMOG, and JNK.Inhibitor.VIII). The prognostic value of the CSRGs was further validated by nomogram plots, which revealed that it was superior to the tumor TNM and pathologic stage. Finally, the three expression levels were evaluated in GES-1, HGC27 and AGS cells by qRT-PCR.